2020
DOI: 10.1111/1750-3841.15379
|View full text |Cite
|
Sign up to set email alerts
|

The potential application of the protein hydrolysates of three medicinal plants: cytotoxicity and functional properties

Abstract: Functional evaluation of encrypted bioactive peptides in protein structure helps to better understand those for using in pharmacy and food sciences. For this purpose, the total protein was extracted from Matricaria chamomilla, Ziziphora clinopodioides, and Cressa cretica, and partially purified with ammonium sulfate. Protein hydrolysates were obtained from pancreatin hydrolysis for 240 min and the enzyme hydrolysis was confirmed using the determination of hydrolysis degree and Fourier transform infrared (FT-IR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 41 publications
0
5
1
Order By: Relevance
“…Besides, the surface tension of other oilseed protein hydrolysates ranged from 64.0 mN/m to 66.0 mN/m, much higher compared to dairy and rapeseed protein hydrolysates. Taghizadeh et al (2020) measured surface tension of protein hydrolysates obtained from three medicinal plants (C.retica, Z.clinopodioides and M.chamomilla) after in vitro gastrointestinal digestion with values being much lower than those in our study, ranging from 48.4 mN/m to 59.6 mN/m). In addition, do Evangelho et al (2017) reported the surface tension of pepsin-treated black bean protein hydrolysates to be below 54.0 mN/m.…”
Section: Surface Tension Measurementcontrasting
confidence: 71%
“…Besides, the surface tension of other oilseed protein hydrolysates ranged from 64.0 mN/m to 66.0 mN/m, much higher compared to dairy and rapeseed protein hydrolysates. Taghizadeh et al (2020) measured surface tension of protein hydrolysates obtained from three medicinal plants (C.retica, Z.clinopodioides and M.chamomilla) after in vitro gastrointestinal digestion with values being much lower than those in our study, ranging from 48.4 mN/m to 59.6 mN/m). In addition, do Evangelho et al (2017) reported the surface tension of pepsin-treated black bean protein hydrolysates to be below 54.0 mN/m.…”
Section: Surface Tension Measurementcontrasting
confidence: 71%
“…Finally, the absorbance was measured at 570 nm using a microplate reader. The cell viability percentage was calculated by the described equation elsewhere [ 26 ] and IC 50 value was calculated.…”
Section: Methodsmentioning
confidence: 99%
“…Triton X-100 was used as a positive control. The IC 50 , GI 50 , and LC 50 values were calculated according to the previously described method [ 18 ].…”
Section: Methodsmentioning
confidence: 99%